Evaluation of Different Drumstick Genotypes (Moringa sp.) Against Salt Stress - Latif, M A; Robbani, M; Akhter, K (The Agriculturists, 2016)
A pot experiment was conducted during March 2012 to February 2013 to evaluate the salt tolerance of drumstick (Moringa sp.) genotypes in a factorial split plot design. Two factors, water salinity was assigned in the main plot with 4 levels (control, 7, 10 and 13 dS/m) and10 drumstick genotypes of Bangladesh (Acc. no. 1 to Acc. no. 10) in the sub-plot with 3 replications. The data were collected for the vegetative growth, percent alive cuttings and necrosis and chlorosis of leaves on the 12thmonth of the study. The results indicated that the Acc. no. 4 from Satkhira and the Acc. no. 5 from Khulna were the best in all respects even at 10 dS/m salinity level. The results also revealed that most of the genotypes performed more or less well up to the 7 dS/m salinity but none at the 13 dS/m. No genotype showed sensitivity to the lowest salinity level. In addition, The highest concentration of total Na+ and Cl- were observed in the shoots and the leaves of the Acc. no. 5 and Acc. no. 9 at 13 dS/m salinity level as well. The Agriculturists 2015; 13(1) 94-100